Retinal photoreceptor ellipsoid zone is a structural biomarker for visual outcome after successful macular hole surgery: A novel grading system-based study - Samya Singh; Sandeep Saxena; Carsten H Meyer; Aman Chandra; Levent Akduman (Indian Journal of Ophthalmology)
Purpose: To develop a novel external limiting membrane (ELM) and ellipsoid zone (EZ) restoration-based grading system after successful macular hole surgery (MHS) and to evaluate EZ as a structural biomarker for the final visual outcome. Methods: In a tertiary care center-based retrospective study, 34 consecutive cases of successful MHS for full-thickness macular holes (FTMHs) were included. Spectral domain optical coherence tomography (SD-OCT) cross-sectional analysis was performed on preoperative and postoperative data of weeks 1, 4, 12, and 24, respectively. Sequential measurements of FTMH size, ELM and EZ defect were performed using the caliper function of SD-OCT. MHS was uniquely graded as grade 0: persistence of ELM and EZ defect; grade 1: partial or complete restoration of ELM with shortening of EZ defect; and grade 2: complete restoration of ELM and EZ. Data were statistically analyzed on Statistical Package for the Social Sciences software-version 24. Results: MHS was graded as grade 0 (n = 8), grade 1 (n = 15), and grade 2 (n = 11). Best corrected visual activity (BCVA) was found to be 1.13 ± 0.19 in grade 0, 0.59 ± 0.09 in grade 1, and 0.26 ± 0.06 in grade 2. One-way analysis of variance showed improvement in final BCVA among the three grades (P < 0.001) Postoperative visual acuity and residual EZ defect had a statistically significant linear correlation (r = 0.899, P < 0.001). EZ was found to be an excellent structural biomarker for final BCVA (area under the curve = 0.99). Conclusion: Successful MHS is associated with better visual outcomes in eyes with restored EZ. ELM restoration preceded EZ regeneration. MHS novel grading system is physician friendly, incorporates pathoanatomic aspects, and correlates well with visual outcomes.